2012
DOI: 10.1002/fuce.201100014
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Gas Diffusion Layers for PEM Fuel Cells

Abstract: The gas diffusion layer (GDL) is a critical component of a proton exchange membrane fuel cell, and can play a key role in fuel cell performance. In order to design reliable and durable fuel cells, knowledge of the GDL microstructure is necessary. Currently, characterization of GDLs is generally based on porosity measurements to obtain a pore size distribution. However, the pore size distribution in GDLs may not be the only factor that affects the fuel cell performance. Additional microstructural characterizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 20 publications
4
54
0
Order By: Relevance
“…To identify the mean fiber lengths in the inplane direction, images of PTL surface were analyzed to identify the fibers and their orientation with respect to one of the orthogonal axis. First, the distribution of fiber lengths and orientation relative to an orthogonal direction was established using the procedure similar to that described in Parikh et al 30 The projected fiber length in the in-plane direction, f , is found by multiplying the mean fiber length by the cosine of the mean fiber orientation. This projected length characterizes the mean, in-plane length over which heat transfer occurs without a fiber-to-fiber contact.…”
Section: In-plane Effective Thermal Conductivitymentioning
confidence: 99%
“…To identify the mean fiber lengths in the inplane direction, images of PTL surface were analyzed to identify the fibers and their orientation with respect to one of the orthogonal axis. First, the distribution of fiber lengths and orientation relative to an orthogonal direction was established using the procedure similar to that described in Parikh et al 30 The projected fiber length in the in-plane direction, f , is found by multiplying the mean fiber length by the cosine of the mean fiber orientation. This projected length characterizes the mean, in-plane length over which heat transfer occurs without a fiber-to-fiber contact.…”
Section: In-plane Effective Thermal Conductivitymentioning
confidence: 99%
“…Poornesh et al [8] found a relationship between the GDL's in-plane mechanical properties and membrane thinning. Parikh et al [9] investigated the relationship between fuel cell efficiency and GDL materials by testing GDL samples from Freudenberg, SGL and Toray. They studied pore size distributions but also size, shape and orientation of the pores.…”
Section: Introductionmentioning
confidence: 99%
“…Parikh et al extracted pore size distribution of SGL, Toray and Freudenberg materials from scanning electron microscopy. 55 An average pore diameter of 31. • , but we assume a higher contact angle of θ = 60…”
Section: Resultsmentioning
confidence: 99%